Analisis Fashion Involvement Dan Emosi Positif Terhadap Impulse Buying Pada Matahari Departmentstore Surabaya - Thyophoida Wanty Suryani Panjaitan; Maria Widyastuti (BIP's JURNAL BISNIS PERSPEKTIF, 2013)
Nowadays more and more women are found working, ii will also change the shopping style of the women, especially in the world of fashion (clothing) is not an exception in the event of pemberan discount programs, such as the anniversary of the city of Surabaya then we can see a lot of customers visit, especially the female consumer. Changes in shopping style is one effect that caused by working world that make people always want to look up to date in fashion. It is one of the triggers of consuments to buy out of plan, where it occurs outside of consciousness due to a moment of emotion when viewing the product and interesting that displayed on store outlets. The purpose of this study is to find out the influence of fashion involvement and partal positive emotions on the Impulse Buying at the Matahari Department Store Surabaya.